Chronic myeloid leukemia patients and treatment-free remission attitudes: a multicenter survey - Lou J; Huang J; Wang Z; Wen B; Tu C; Huang W; Zhai Z; Du X (Patient Preference and Adherence, 2018)
Jin Lou,1,2 Junjie Huang,1 Zitong Wang,3 Bingbing Wen,1 Chuanqing Tu,4 Wangxiang Huang,5 Zhimin Zhai,2 Xin Du1 1Department of Hematology, Shenzhen Second People’s Hospital, The First Affiliated Hospital of Shenzhen University, Shenzhen 518000, China; 2Department of Hematology, The Second Affiliated Hospital of Anhui Medical University, Hefei 230601, China; 3School of Medicine, University of Sydney, Sydney, NSW, Australia; 4Department of Hematology, People’s Hospital of Baoan District, Shenzhen 518101, China; 5Department of Hematology, Longgang District Central Hospital of Shenzhen, Shenzhen 518116, China Background: Treatment-free remission (TFR) is becoming an essential goal for chronic myeloid leukemia (CML) patients in clinical practice. Few studies have emphasized patient attitudes or preferences about discontinuing tyrosine kinase inhibitors treatment. This study aimed to evaluate the characteristics of Chinese CML patients and their views and perspectives on TFR. Methods: A total of 329 CML patients participated in this multicenter, questionnaire-based, standardized, semi-structured, interview-guided, open-ended, cross-sectional study. Information about demographics, diagnosis information, treatment history, quality of life (QoL), and TFR preference was collected. Results: The adherence rate was 50% (N=163) and sex dependent (males, OR=2.24, 95% CI=1.40–3.58). Physical activity, symptom burden, mood impact, and daily impact were found to be better among adherent patients. Thirty-four percent of the patients were willing to attempt TFR positively. The reasons for preferring TFR were due to side effects (56%) followed by high cost (52%), inconvenience (42%), and pregnancy need (41%). Multivariate analysis indicated that patients who were younger (OR=0.96, 95% CI=0.94–0.99) with shorter disease duration (OR=0.90, 95% CI=0.82–0.98) and higher disease symptom burden (OR=1.08, 95% CI=0.98–1.21) were more likely positive about TFR. Conclusion: Patients who were younger with shorter disease duration and higher disease symptom burden were more likely to try TFR. They expressed several perceived noncost factors of TFR. Our data may help promote the management of CML and designing of clinical trials for TFR in some developed regions of China. Keywords: CML, TKI, TFR, preference, perception